Governance of protected areas in the Arctic - Koivurova, Timo (Utrecht Law Review, 2009)
This article analyzes what has been achieved in the Arctic cooperation process – now functioning as the Arctic Council – as regards protected areas in the region. Specifically, the research examines how the work in two of the working groups of the Arctic Council has evolved – the Conservation of Arctic Flora and Fauna (CAFF) and the Protection of the Arctic Marine Environment (PAME). Of particular interest here is CAFF’s Circumpolar Protected Area Network (CPAN), which is designed to coordinate the protected area policies of the Arctic states in their Arctic regions. The main goal of the article is to examine what kinds of functions CPAN is meant to achieve and to discuss whether the project has met its goals. An additional focus is the most recent development in the Arctic Council in the field of marine protected areas (MPAs), which were adopted as one priority action for another working group of the Council, the Protection of the Arctic Marine Environment. All of the developments discussed are evaluated by first identifying the trajectories of protected area activities in the Arctic Council and then discussing the possible ways forward. One salient consideration here is whether normative platforms other than the Arctic Council are better equipped to promote the work on protected areas in the Arctic and what type of policy focus for protected areas could be assumed in the Council.